TRANSYT COORDINATION OF TRAFFIC SIGNALS IN BANDUNG - Sudiyono, D.Denni
TRANSYT is a method of determining the green splits and relative timings (offsets) of traffic signals in an area so as to minimise the cost of operating vehicles on the traffic network. The performance index is a weighted function of the sum of the cost of travel on a link, the cost of each stop, and the cost of each unit of delay time. Typically, the performance index is to be minimised. The method uses a simple but effective model of the traffic on a specified network. Optimisation procedures are available in the TRANSYT model to determine the best signal settings based on minimising the performance index for the network. The application of the TRANSYT version 8 program to the Bandung Central Business District traffic network showed that this program could be applied successfully with significant improvement to traffic flow. Compared with the existing condition of Bandung traffic, the parameters resulting from analysis by TRANSYT all showed improvement: the total distance travelled would not significantly change; the total vehicular time spent in the network would decrease by 35%; the total delay to vehicular traffic would decrease by 67%; and the system. speed would increase by 51%. Modification of three unsignalised intersections, to be provided with signals o.n the network, appeared not to give significant improvement. This was believed to occur because the links which presently have (or exact) priority have unbalanced flows which take precedence over the present give-waylinks at these three intersections. However, traffic signals at the three presently unsignalised intersections would result in higher speeds on most arterials. Proposed speeds can be obtained by assigning values of cruise speed in the input data. It was found that the performance index is less sensitive to changes in saturation flow than to changes in assigned cruise speed. Limited data and, initiallydifficulties with computer operation decreased the efficaciousness of application of the program. Field evaluation before and after implementation of TRANSYT signal timings would be needed to assess the advantages and possible disbenefits of coordinating the traffic signals in a busy road network.